PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA KARYAWA PT. BSI ACEH TENGGARA - Cici Ratnasari; Sabitah Sabitah; Rila Maufira (Jurnal Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of training and motivation on employee performance at PT. BSI Aceh Tenggara. The background of this research is based on the importance of human resource (HR) quality in supporting organizational success, particularly in the Islamic banking sector, which upholds high service standards rooted in Islamic values. Effective training and high work motivation are believed to enhance employee competence and productivity. This research uses a quantitative approach with a survey method involving the entire population of employees at PT. BSI Aceh Tenggara, totaling 10 respondents, through a saturated sampling technique. Data were collected using questionnaires and analyzed using validity and reliability tests as well as multiple linear regression analysis. The results show that both training and motivation have a significant effect on employee performance, both partially and simultaneously. Classical assumption tests, including normality, multicollinearity, autocorrelation, and heteroscedasticity, indicate that the regression model meets statistical requirements. The F-test results demonstrate that training and motivation together have a significant impact on employee performance, while the t-test confirms that each independent variable contributes positively. These findings affirm that investment in proper training and motivation strategies is an effective way to enhance employee performance. This research provides practical implications for the management of PT. BSI Aceh Tenggara in formulating sustainable human resource development policies aligned with Islamic principles